Interaction of the mitotic kinesin Eg5 inhibitor monastrol with P-glycoprotein - Peters, Tanja; Lindenmaier, Heike; Haefeli, Walter E.; Weiß, Johanna (Naunyn-Schmiedeberg's archives of pharmacology, 2006)
Monastrol is the first characterised small molecule inhibitor of the motor protein Eg5 involved in bipolar mitotic spindle assembly. Eg5 localises to microtubules in mitosis, but not to interphase microtubules, suggesting that Eg5 inhibitors may be useful to specifically target proliferating tumour tissue, thereby avoiding dose-limiting neuropathy observed with other antimicrotubule agents like taxanes or vinca alkaloids. Because other antimicrotubule agents fail in multidrug resistance associated with P-glycoprotein (Pgp) over-expression, we investigated the interaction of monastrol with Pgp in vitro. By means of the calcein assay (with P388/dx cells and primary porcine brain capillary endothelial cells) and confocal laser-scanning microscopy (with L-MDR1 cells) we demonstrated that monastrol is a weak inhibitor of Pgp in vitro, with f2 values being about two orders of magnitude greater than those of the well-known inhibitors verapamil and quinidine. Monastrol also induces Pgp in vitro as measured by mRNA expression in LS180 cells after incubation with monastrol. However, its effect is weak compared to rifampicin. Whilst it reveals weak inhibitory and inductive characteristics, monastrol appears to be not transported by Pgp, as indicated by the lack of difference in the antiproliferative effect of this compound in cell lines with and without over-expression of Pgp. The observed interaction profile of monastrol with Pgp is promising for the development of other more potent Eg5 inhibitors.